Cultura e clima organizacionais - Lunardi Filho, Wilson Danilo (SINERGIA - Revista do Instituto de Ciências Econômicas, Administrativas e Contábeis, 2011)
This paper consists in a brief bibliographic revision about Organizational Culture and Climate. It intents to show, of synthetical and organizated form, the thoughts and ideas of the consulted authors that study contribute with elucidating points to differenciation between organizational Culture and Climate.